Integrative review on medicinal plants in the treatment of obesity and dyslipidemias on climacteric women (Research, Society and Development, 2022)
Medicinal plants and herbal medicines are widely used in Brazil as a therapeutic alternative, especially by those who are being treated for chronic diseases such as obesity and dyslipidemia, common diseases that are present in climacteric women. The objective of this work was to carry out an integrative review to identify species of medicinal plants used as a complementary therapy for the treatment of obesity and dyslipidemia in climacteric women. For this work, a bibliographic review was carried out with a survey of scientific articles in order to produce a qualitative database with criteria that allowed to gather, evaluate and synthesize the results of previous studies relevant to the theme medicinal plants, obesity, dyslipidemias and women in the climacteric. The results describe the identification of species, uses, active ingredient, forms of use, dose of use, toxicity of the species found. Among the species mentioned are: Camellia sinensis (L) O. Kuntze, Garcinia cambogia (Gaertn.) Desr., Citrus aurantium Dulcis (Citrus sinensis (L) Osbeck, Cordia salicifolia Cham, Gymnema sylvestre [Retz] R. Br. Ex Schult ), Phaseolus vulgaris L., Hibiscus sabdariffa D.C., Ilex paraguariensis A. St.-Hil, Equisetum arvense L, Cassia nomame (Sieb) Honda. These are species rich in antioxidants, with different actions in the body. The indication of these species by nutritionists can collaborate in the treatment of obesity as a complementary therapy for climacteric women, concomitant with adequate diet and physical activity.